The Rise of Finfluencers: A Digital Transformation in Investment Advice - Shailendra Singh; Mahesh Sarva (Australasian Accounting, Business and Finance Journal, 2024)
The primary aim of this study is to investigate the extent to which finfluencers can be considered experts who fulfill the critical role of information intermediaries contributing to the efficiency of financial markets. To assess this, we assembled a manually collected dataset consisting of recommendations made by finfluencers. We conducted an event study to analyze both short-term and long-term effects on stocks. The findings reveal that, on average, all stocks examined during the event window [-10, +10] days exhibit a noteworthy Cumulative Abnormal Announcement Return (CAAR). The outcome suggests that, in the short term, finfluencers may not be deemed as experts. In contrast, the long-term Buy-and-Hold Abnormal Returns (BHAR) were positive and also statistically significant. Considering these results and the frequent absence of financial licenses among finfluencers, along with their tendency to endorse risky investments, we endorse SEBI's action in issuing a consultation paper (dated 25th August 2023) to regulate unregistered finfluencers. These measures are aimed at safeguarding inexperienced investors from taking undue risks and ensuring the integrity of financial markets.
Keywords: SEBI; Finfluencers; Experts; Market Efficiency; Event Study